2014
DOI: 10.1063/1.4862679
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of photosensitive surfactant with DNA and poly acrylic acid

Abstract: In this paper, we investigate interactions and phase transitions in polyelectrolyte-surfactant complexes formed between a cationic azobenzene-containing surfactant and two types of polyelectrolytes: natural (DNA) or synthetic (PAA: poly acrylic acid). The construction of a phase diagram allowed distancing between four major phases: extended coil conformation, colloidally stable compacted globules, colloidal instability range, and surfactant-stabilized compact state. Investigation on the complexes' properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…The photoisomerization behavior of the surfactant is described in detail elsewhere22. In short, in the dark state ( trans conformation) of the surfactant is characterized by an absorption band with a maximum at 353 nm, while the cis isomer is characterized by two absorption bands with maxima at 313 nm and at 437 nm (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photoisomerization behavior of the surfactant is described in detail elsewhere22. In short, in the dark state ( trans conformation) of the surfactant is characterized by an absorption band with a maximum at 353 nm, while the cis isomer is characterized by two absorption bands with maxima at 313 nm and at 437 nm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Along with the conformational changes, the physical properties of the molecules are also altered: their shape switches from rod-like to “Γ -like” with a corresponding increase in free volume, the dipole moment increases from 0 Debye in the trans- to ~3 Debye in the cis- conformation. When incorporated into the hydrophobic tail of a surfactant molecule, photoisomerization can thus alter the hydrophobicity/hydrophilicity of the whole surfactant structure18, and can be toggled by alternating illumination with UV and blue light19. In this way, azobenzene containing surfactant bears an enormous potential for practical applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] Fig. 1 shows schematically such phase diagram; The transitions are also typical for azobenzene containing surfactant complexes with other polyelectrolytes.…”
Section: Introductionmentioning
confidence: 92%
“…Detailed dynamic light scattering (DLS) studies proved that this transition corresponds to the DNA compaction, which takes place before DNA charge compensation. 41 The complete DNA compaction was demonstrated when only 20% of its charge is compensated by the photosensitive surfactant (Z ≈ 0.2). It was also shown that such behavior is not only inherent to DNA but typical for other polyelectrolytes such as poly(acrylic acid), which can be compacted at Z ≈ 0.5.…”
Section: Introductionmentioning
confidence: 99%